SISTEM LAYANAN HYBRID CLOUD STORAGE DENGAN OWNCLOUD PADA DEBIAN 9 - Santoso, Santoso; Siagian, Saut (Jurnal Sistem Informasi Kaputama (JSIK), 2021)
Previous private cloud storage service systems were only limited to testing services from a simple design that could be run locally. Development from private to hybrid and linked to internet publishing to be used for public services. The purpose of this research is to develop servers and storage service systems based on online (cloud storage) and users who are private data and public data can take advantage of cloud storage services that can be accessed anywhere connected to the internet. The research method in this study used the Evaluative Research and Development (R&D) method. This research will be published by an accredited National Journal.